2016
DOI: 10.1051/matecconf/20166501004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model and Analysis of Asymmetric Telescopic Wing for Morphing Aircraft

Abstract: Abstract. Morphing aircraft has been the research hot topics of new concept aircrafts in aerospace engineering. Telescopic wing is an important morphing technology for morphing aircraft. This paper describes the dynamic equations and kinematic equations based on theorem of momentum and theorem of moment of momentum, which are available for all morphing aircrafts. Meanwhile,as simplified , dynamic equations for rectangular telescopic wing are presented. In order to avoid the complexity using aileron to generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In contrast, an aircraft with a small wingspan can offer higher flight speeds and better manoeuvrability (25) . The asymmetric telescopic wingspan technique can be employed for roll control instead of using conventional control surfaces (26,27) . However, the constant challenge facing designers regarding variable span morphing wing design is to overcome the weight penalty as well as its design complexity (28) .…”
Section: Design and Modelling Of The Mvstw Modelmentioning
confidence: 99%
“…In contrast, an aircraft with a small wingspan can offer higher flight speeds and better manoeuvrability (25) . The asymmetric telescopic wingspan technique can be employed for roll control instead of using conventional control surfaces (26,27) . However, the constant challenge facing designers regarding variable span morphing wing design is to overcome the weight penalty as well as its design complexity (28) .…”
Section: Design and Modelling Of The Mvstw Modelmentioning
confidence: 99%
“…Tong and Ji [5] have established the dynamic model and explored using the idea of roll control through asymmetric sweep angle change rather than traditional aileron in the flight control design. Chen et al [6] have developed the dynamic and kinematic equations of asymmetric telescopic wing aircraft. Analysis results have shown that telescopic wings behave better roll performance in the case of a large angle of attack and lift.…”
Section: Velocity Potentialmentioning
confidence: 99%